Pelatihan Sistem Administrasi Berbasis Digital untuk Meningkatkan Kesiapan Kerja Siswa - Muhtajuddin Danny; Asep Muhidin; Basar Maringan Hutauruk; Amat Damuri; Hendri Rahman; Nur Hidayati (VINICHO MEDIA PUBLISINDO, 2026)
The rapid growth of digital transformation has shifted office administration from conventional manual processes to technology-based systems, requiring vocational high school (SMK) graduates to possess digital administrative competencies aligned with industry demands. However, a preliminary assessment conducted at SMK Garuda Nusantara revealed that students still experience limitations in using digital administrative applications, managing electronic archives, utilizing cloud-based collaboration platforms, and applying administrative skills in real workplace contexts. This community service program aims to enhance students’ digital administrative competencies and work readiness through practice-oriented training. The implementation method consists of program socialization, hands-on and project-based training, technology implementation through digital administration case studies, mentoring, evaluation using pre-test and post-test, and sustainability planning. The expected outputs include improved student competencies, the development of a digital administration training module, students’ digital portfolios, implementation guidelines for digital administration, and recommendations for technology-based learning development within the school. This program is expected to improve students’ employability while supporting the digital transformation of administrative learning in vocational education